Effect of sorbitol, L-sorbose and inositol on myo-inositol-1-phosphate synthase activity in Neurospora crassa strains - A. Kiss; A. Zsindely; M. Schablik; G. Szabo (Fungal Genetics Reports, 1984)
Effect of sorbitol, L-sorbose and inositol on myo-inositol-1-phosphate synthase activity in Neurospora crassa strains